Ardealite baking-free brick and preparation method thereof
By using a large proportion of pretreated phosphogypsum and a specific proportion of slag, steel slag, and palm fiber, combined with a composite alkali trigger, phosphogypsum is prepared, which solves the problem of small amount of phosphogypsum and low resource utilization rate and The problem of low product strength achieves the effects of high strength, low water absorption rate and low environmental pollution.
Patent Information
- Application Number
- CN202411635260.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, phosphogypsum is small, resource utilization rate is low, phosphogypsum is low in strength, and the pretreatment process investment is high, wastewater treatment costs and energy consumption are high.
A larger proportion of pretreated phosphogypsum is used, combined with a specific proportion of slag, steel slag, and palm fiber, and is stimulated by composite alkali triggers to prepare phosphogypsum without burning bricks. The pretreatment method includes hydrothermal reaction of phosphogypsum, straw ash and polyacrylamide at 60-80°C, dry and grinding to obtain the pretreated phosphogypsum.
The prepared phosphogypsum burn-free bricks have high mechanical strength, low water absorption, low freeze-thaw strength loss rate and low freeze-thaw mass loss rate, which meet the requirements of wall materials. At the same time, the resource utilization rate of phosphogypsum is improved, environmental pollution is reduced, and production costs are reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid waste recycling, and in particular to a phosphogypsum unfired brick and a preparation method thereof. Background Art
[0002] Unburned bricks are a new type of building material produced by physical pressing or chemical curing methods. They have the advantages of high strength and high durability and are widely used in construction, roads, gardens and other fields. Compared with ordinary clay fired bricks, unburned bricks do not require high-temperature sintering during the production process and can be used after simple molding and maintenance processes. Therefore, unburned bricks have the characteristics of energy saving, emission reduction, and environmental protection, and have become a highly respected green and environmentally friendly building material in the modern construction industry.
[0003] Common unfired bricks made from industrial waste residues in the market mainly include fly ash bricks, lime sand bricks, slag bricks, etc. Phosphogypsum is an industrial waste residue produced when phosphoric acid is produced by the wet process in the phosphorus chemical industry. About 5 tons of phosphogypsum are produced for every 1 t of phosphoric acid produced. At present, phosphogypsum is mainly treated by stockpiling. The phosphogypsum yard not only occupies a large amount of land resources, but also poses safety hazards and environmental pollution risks. As an industrial by-product with cementitious properties, phosphogypsum itself has the natural characteristics of producing unfired bricks and has been initially used in the preparation of unfired brick products. The resource utilization of phosphogypsum unfired bricks can help the phosphorus chemical industry transform towards green and sustainable development. At the same time, it has important practical significance for ecological environmental protection and resource conservation.
[0004] However, there are still some shortcomings in the existing technology of using phosphogypsum to produce unfired bricks, mainly manifested in: small amount of phosphogypsum, low resource utilization rate; low strength of phosphogypsum unfired brick products. In addition, some existing technologies use water washing, calcination and other methods to pre-treat phosphogypsum before preparing unfired bricks, which has problems such as high investment, high wastewater treatment cost, and high energy consumption. Summary of the invention
[0005] In view of the deficiencies in the above prior art, the present invention provides a phosphogypsum unfired brick and a preparation method thereof. The present invention adopts a larger amount of phosphogypsum, and the prepared phosphogypsum unfired brick has high strength and low water absorption, which can meet the use requirements of wall materials.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] A phosphogypsum unburned brick, the raw materials, calculated by weight percentage, include: 60% to 80% of pretreated phosphogypsum, 0.5% to 2% of palm fiber, 10% to 30% of slag, 5% to 15% of steel slag, 1% to 5% of cement, and 2% to 5% of a composite alkali activator;
[0008] The method for pretreating the phosphogypsum is as follows: subjecting the phosphogypsum, straw ash and polyacrylamide to a hydrothermal reaction at 60-80° C., drying and then grinding to obtain the pretreated phosphogypsum.
[0009] The present invention adopts a large proportion of pretreated phosphogypsum, and then matches it with a specific proportion of slag, steel slag, and palm fiber, and excites it through a composite alkali activator, so that the prepared phosphogypsum unburned brick has excellent properties such as high mechanical strength and low water absorption. The present invention adopts a specific method to pretreat phosphogypsum, which can reduce the concentration of P, F and organic matter in phosphogypsum, reduce environmental pollution, and at the same time, improve the pH of phosphogypsum and increase the reactivity of phosphogypsum; in addition, phosphogypsum reacts with straw ash containing amphoteric oxides and polyacrylamide with strong flocculation ability, thereby improving the removal efficiency of pollutants in phosphogypsum, and generating a network structure with higher polymer performance, which is beneficial to improving the performance of phosphogypsum. In the preparation of phosphogypsum unfired bricks, the sulfate in phosphogypsum can stimulate the activity of slag and steel slag, causing a volcanic ash reaction. The generated hydration products mainly include CSH gel and dense calcium vanadium, which can improve the density and strength; at the same time, the composite alkali activator is mainly composed of alkaline materials, which can play an stimulating role again, making the hydration reaction of the mixture more complete and the activity of steel slag more released; cement, as a hydraulic cementing material, further plays a gelling role and promotes the improvement of strength; palm fiber can enhance the strength of phosphogypsum unfired bricks, improve their durability, and make phosphogypsum unfired bricks have the characteristics of low water absorption.
[0010] Furthermore, the raw materials of the phosphogypsum unfired brick include, by weight percentage: 70% pretreated phosphogypsum, 0.5% palm fiber, 10% slag, 10% steel slag, 4.5% cement, and 5% composite alkali activator.
[0011] Furthermore, the weight ratio of the phosphogypsum, straw ash and polyacrylamide is 100:(1-5):(0.2-1).
[0012] Furthermore, the average molecular weight of the polyacrylamide is 4 million to 20 million.
[0013] Furthermore, the hydrothermal reaction time is 3 to 5 h.
[0014] Furthermore, the composite alkali activator is a mixture of limestone, sodium sulfate and potassium hydroxide, and the weight ratio of the limestone, sodium sulfate and potassium hydroxide is (2-3): (2-3): (4-6).
[0015] Furthermore, the diameter of the palm fiber is 200-500 μm, and the length is 15%-30% of the minimum size (length, width and height) of the phosphogypsum unfired brick.
[0016] The present invention also provides a method for preparing the phosphogypsum unfired brick, comprising the following steps:
[0017] S1. Mixing: Steel slag, slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, slag and composite alkali activator be 500~600 m 2 / kg, then add pretreated phosphogypsum, cement and palm fiber and mix evenly, let stand for 16-30 hours to obtain dry mix;
[0018] S2, pressing and molding: adding an appropriate amount of water to the dry mix, mixing evenly and pressing and molding to obtain a brick;
[0019] S3. Demoulding and curing: After demolding, the bricks are placed indoors for natural curing for 7 to 14 days to obtain phosphogypsum unfired bricks.
[0020] Furthermore, in step S2, the amount of water added is 8% to 12% of the weight of the dry mix, and the moisture content of the brick is controlled within 15%; if the moisture content is too high, the brick will stick to the inside of the mold, making demolding inconvenient.
[0021] Furthermore, in step S2, the pressing method is static pressing; the static pressing pressure is 10-30 MPa, and the pressure is maintained for 1-3 min. The pressure of static pressing is an important factor affecting the density and strength of the brick body. Therefore, it is necessary to select a pressing device that can provide stable and adjustable pressure to ensure that the brick body is evenly pressed during the pressing process; during the pressing process, it is necessary to monitor the pressure parameters in real time and make timely adjustments according to the characteristics of the raw materials and the molding effect to ensure the best pressing effect.
[0022] Compared with the prior art, the present invention is beneficial in that:
[0023] (1) The phosphogypsum unfired bricks provided by the present invention have excellent properties such as high mechanical strength and low water absorption, among which the compressive strength is greater than 22 MPa, the water absorption is less than 8%, the softening coefficient is greater than 0.85, the freeze-thaw strength loss rate is less than 10%, and the freeze-thaw mass loss rate is less than 3%.
[0024] (2) The phosphogypsum unfired bricks provided by the present invention have a large proportion of phosphogypsum, high solid waste utilization, are conducive to large-scale disposal, reduce environmental pollution, and have broad market application prospects.
[0025] (3) The present invention adopts a semi-dry pressing method to prepare phosphogypsum unfired bricks, which does not require high-temperature sintering, has low production costs and high economic benefits. In addition, the preparation process is simple, safe and environmentally friendly, and is conducive to large-scale production. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention provides a phosphogypsum unburned brick, wherein the raw materials include, by weight percentage: 60% to 80% of pretreated phosphogypsum, 0.5% to 2% of palm fiber, 10% to 30% of slag, 5% to 15% of steel slag, 1% to 5% of cement, and 2% to 5% of a composite alkali activator;
[0028] The method for pretreating the phosphogypsum is as follows: subjecting the phosphogypsum, straw ash and polyacrylamide to a hydrothermal reaction at 60-80° C., drying and then grinding to obtain the pretreated phosphogypsum.
[0029] In some examples, the weight ratio of the phosphogypsum, straw ash, and polyacrylamide is 100:(1-5):(0.2-1).
[0030] In some examples, the average molecular weight of the polyacrylamide is 4 million to 20 million.
[0031] In the following specific examples, the average molecular weight of the polyacrylamide is 8 million.
[0032] In some examples, the hydrothermal reaction time is 3 to 5 h.
[0033] In some examples, the composite alkali activator is a mixture of limestone, sodium sulfate and potassium hydroxide, and the weight ratio of the limestone, sodium sulfate and potassium hydroxide is (2-3): (2-3): (4-6).
[0034] In the following specific examples, the weight ratio of the limestone, sodium sulfate and potassium hydroxide is 2.5:2.5:5.
[0035] In some examples, the diameter of the palm fiber is 200-500 μm, and the length is 15%-30% of the minimum size (length, width and height) of the phosphogypsum unfired brick.
[0036] In the following specific examples, the size of the prepared phosphogypsum unfired brick is 240 mm x 115 mm x 53 mm; the diameter of the palm fiber is 300 μm and the length is 10 mm.
[0037] Example 1
[0038] A phosphogypsum unburned brick, the raw materials, calculated by weight percentage, include: 70% pre-treated phosphogypsum, 0.5% palm fiber, 10% slag, 10% steel slag, 4.5% cement, and 5% composite alkali activator;
[0039] The preparation method of phosphogypsum unfired brick is as follows:
[0040] (1) Pretreatment of phosphogypsum: phosphogypsum, straw ash and polyacrylamide in a weight ratio of 100:2:1 were hydrothermally reacted at 70°C for 4 h, dried and ground into powder to obtain pretreated phosphogypsum.
[0041] (2) Mixing: Steel slag, mineral slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, mineral slag and composite alkali activator to be 500 m 2 / kg, then add pretreated phosphogypsum, cement and palm fiber and mix evenly, and let stand for 24 hours to obtain a dry mix;
[0042] (3) Pressing and molding: Add an appropriate amount of water to the dry mixture, mix well, and then press it through a high-pressure molding machine at 20 MPa for 2 min to obtain a brick. The moisture content of the brick is 13%.
[0043] (4) Demolding and curing: Demolding is carried out immediately after pressing and the bricks are placed indoors for natural curing for 10 days to obtain phosphogypsum unfired bricks.
[0044] Example 2
[0045] A phosphogypsum unburned brick, the raw materials, by weight percentage, include: 80% of pretreated phosphogypsum, 1% of palm fiber, 10% of slag, 5% of steel slag, 1% of cement, and 3% of composite alkali activator;
[0046] The preparation method of phosphogypsum unfired brick is as follows:
[0047] (1) Pretreatment of phosphogypsum: phosphogypsum, straw ash and polyacrylamide in a weight ratio of 100:5:0.2 were hydrothermally reacted at 70 °C for 4 h, dried and ground into powder to obtain pretreated phosphogypsum.
[0048] (2) Mixing: Steel slag, mineral slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, mineral slag and composite alkali activator be 500 m 2 / kg, then add the pretreated phosphogypsum, cement and palm fiber, mix evenly, and let it stand for 24 hours to obtain a dry mix.
[0049] (3) Pressing and molding: Add an appropriate amount of water to the dry mixture, mix well, and then press it through a high-pressure molding machine at 20 MPa for 2 min to obtain a brick. The moisture content of the brick is 13%.
[0050] (4) Demolding and curing: Demolding is carried out immediately after pressing and the bricks are placed indoors for natural curing for 10 days to obtain phosphogypsum unfired bricks.
[0051] Example 3
[0052] A phosphogypsum unburned brick, the raw materials, by weight percentage, include: 60% pretreated phosphogypsum, 2% palm fiber, 18% slag, 13% steel slag, 5% cement, and 2% composite alkali activator; the raw materials include dry mix and palm fiber; wherein the dry mix has the following components: 60% pretreated phosphogypsum, 20% slag, 13% steel slag, 5% cement, and 2% composite alkali activator;
[0053] The preparation method of phosphogypsum unfired brick is as follows:
[0054] (1) Pretreatment of phosphogypsum: phosphogypsum, straw ash and polyacrylamide in a weight ratio of 100:1:1 were hydrothermally reacted at 70°C for 4 h, dried and ground into powder to obtain pretreated phosphogypsum.
[0055] (2) Mixing: Steel slag, mineral slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, mineral slag and composite alkali activator be 500 m 2 / kg, then add the pretreated phosphogypsum, cement and palm fiber, mix evenly, and let it stand for 24 hours to obtain a dry mix.
[0056] (3) Pressing and molding: Add an appropriate amount of water to the dry mixture, mix well, and then press it through a high-pressure molding machine at 20 MPa for 2 min to obtain a brick. The moisture content of the brick is 13%.
[0057] (4) Demolding and curing: Demolding is carried out immediately after pressing and the bricks are placed indoors for natural curing for 10 days to obtain phosphogypsum unfired bricks.
[0058] Comparative Example 1
[0059] A phosphogypsum unburned brick, the raw materials, by weight percentage, include: 70% of pretreated phosphogypsum, 0.5% of palm fiber, 10% of slag, 10% of steel slag, 4.5% of cement, and 5% of composite alkali activator;
[0060] The preparation method of phosphogypsum unfired brick is as follows:
[0061] (1) Pretreatment of phosphogypsum: phosphogypsum and straw ash in a weight ratio of 100:2 were subjected to hydrothermal reaction at 70 °C for 4 h, dried and ground into powder to obtain pretreated phosphogypsum.
[0062] (2) Mixing: Steel slag, mineral slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, mineral slag and composite alkali activator be 500 m 2 / kg, then add the pretreated phosphogypsum, cement and palm fiber, mix evenly, and let it stand for 24 hours to obtain a dry mix.
[0063] (3) Pressing and molding: Add an appropriate amount of water to the dry mixture, mix well, and then press it through a high-pressure molding machine at 20 MPa for 2 min to obtain a brick. The moisture content of the brick is 13%.
[0064] (4) Demolding and curing: Demolding is carried out immediately after pressing and the bricks are placed indoors for natural curing for 10 days to obtain phosphogypsum unfired bricks.
[0065] Comparative Example 2
[0066] A phosphogypsum unburned brick, the raw materials, calculated by weight percentage, include: 70% pre-treated phosphogypsum, 0.5% palm fiber, 10% slag, 10% steel slag, 4.5% cement, and 5% composite alkali activator;
[0067] The preparation method of phosphogypsum unfired brick is as follows:
[0068] (1) Pretreatment of phosphogypsum: phosphogypsum and polyacrylamide in a weight ratio of 100:1 were subjected to hydrothermal reaction at 70 °C for 4 h, dried and ground into powder to obtain pretreated phosphogypsum.
[0069] (2) Mixing: Steel slag, mineral slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, mineral slag and composite alkali activator be 500 m 2 / kg, then add the pretreated phosphogypsum, cement and palm fiber, mix evenly, and let it stand for 24 hours to obtain a dry mix.
[0070] (3) Pressing and molding: Add an appropriate amount of water to the dry mixture, mix well, and then press it through a high-pressure molding machine at 20 MPa for 2 min to obtain a brick. The moisture content of the brick is 13%.
[0071] (4) Demolding and curing: Demolding is carried out immediately after pressing and the bricks are placed indoors for natural curing for 10 days to obtain phosphogypsum unfired bricks.
[0072] Comparative Example 3
[0073] A phosphogypsum unburned brick, the raw materials, by weight percentage, include: 70% of pretreated phosphogypsum, 0.5% of palm fiber, 10% of slag, 10% of steel slag, 4.5% of cement, and 5% of composite alkali activator;
[0074] The preparation method of phosphogypsum unfired brick is as follows:
[0075] (1) Pretreatment of phosphogypsum: phosphogypsum, straw ash and polyacrylamide are mixed in a weight ratio of 100:2:1 and ground into powder to obtain pretreated phosphogypsum.
[0076] (2) Mixing: Steel slag, mineral slag and composite alkali activator are mixed in proportion and then ball milled to make the specific surface area of the mixture of steel slag, mineral slag and composite alkali activator be 500 m 2 / kg, then add the pretreated phosphogypsum, cement and palm fiber, mix evenly, and let it stand for 24 hours to obtain a dry mix.
[0077] (3) Pressing and molding: Add an appropriate amount of water to the dry mixture, mix well, and then press it through a high-pressure molding machine at 20 MPa for 2 min to obtain a brick. The moisture content of the brick is 13%.
[0078] (4) Demolding and curing: Demolding is carried out immediately after pressing and the bricks are placed indoors for natural curing for 10 days to obtain phosphogypsum unfired bricks.
[0079] According to GB / T 2542-2012 “Test Methods for Wall Bricks”, relevant index tests were carried out on the phosphogypsum unfired bricks prepared in Examples 1 to 3 and Comparative Examples 1 to 3. The test results are shown in Table 1.
[0080] Table 1: Performance test results of phosphogypsum unfired bricks
[0081]
[0082] As can be seen from Table 1, the present invention uses straw ash and polyacrylamide to pretreat phosphogypsum under heating conditions, and then matches slag, steel slag, and palm fiber in a specific proportion, and excites through a composite alkali activator to prepare the phosphogypsum unfired brick, which has a compressive strength greater than 22 MPa, a water absorption rate of less than 8%, a softening coefficient greater than 0.85, a freeze-thaw strength loss rate of less than 10%, and a freeze-thaw mass loss rate of less than 3%; while only using polyacrylamide and phosphogypsum for pretreatment under heating conditions (Comparative Example 1), or only using straw ash and phosphogypsum for pretreatment under heating conditions (Comparative Example 2), or simply mixing straw ash, polyacrylamide and phosphogypsum (Comparative Example 3), none of them can effectively improve the performance of phosphogypsum unfired bricks.
[0083] In summary, the present invention adopts a specific method to pretreat phosphogypsum, and then matches slag, steel slag, and palm fiber in a specific proportion, and excites it through a composite alkali activator. The prepared phosphogypsum unfired brick has excellent properties such as high strength, low water absorption, high softening coefficient, and low freeze-thaw strength loss rate; in the phosphogypsum unfired brick of the present invention, the proportion of phosphogypsum is large, the solid waste utilization is high, it is conducive to large-scale disposal, and reduces environmental pollution. Moreover, the preparation process of the phosphogypsum unfired brick of the present invention is simple, safe and environmentally friendly, and is conducive to large-scale production.
[0084] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A phosphogypsum unfired brick, characterized in that: The raw materials, calculated by weight percentage, include: 60% to 80% of pretreated phosphogypsum, 0.5% to 2% of palm fiber, 10% to 30% of slag, 5% to 15% of steel slag, 1% to 5% of cement, and 2% to 5% of composite alkali activator; The method for pretreating the phosphogypsum is as follows: subjecting the phosphogypsum, straw ash and polyacrylamide to a hydrothermal reaction at 60-80° C., drying and then grinding to obtain the pretreated phosphogypsum.
2. The phosphogypsum unfired brick according to claim 1, characterized in that: The raw materials, calculated by weight percentage, include: 70% pre-treated phosphogypsum, 0.5% palm fiber, 10% slag, 10% steel slag, 4.5% cement, and 5% composite alkali activator.
3. The phosphogypsum unfired brick according to claim 1, characterized in that: The weight ratio of the phosphogypsum, straw ash and polyacrylamide is 100:(1-5):(0.2-1).
4. The phosphogypsum unfired brick according to claim 1, characterized in that: The hydrothermal reaction time is 3 to 5 hours.
5. The phosphogypsum unfired brick according to claim 1, characterized in that: The composite alkali activator is prepared by mixing limestone, sodium sulfate and potassium hydroxide, wherein the weight ratio of the limestone, sodium sulfate and potassium hydroxide is (2-3): (2-3): (4-6).
6. The phosphogypsum unfired brick according to claim 1, characterized in that: The diameter of the palm fiber is 200-500 μm, and the length is 15%-30% of the minimum size of the phosphogypsum unfired brick.
7. A method for preparing a phosphogypsum unfired brick according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Mix steel slag, slag and composite alkali activator in proportion and then ball-mill them, then add pretreated phosphogypsum, cement and palm fiber and mix them evenly, and let them stand for 16 to 30 hours to obtain a dry mix; S2, adding an appropriate amount of water to the dry mix, mixing evenly and pressing to form a brick; S3. Placing the bricks indoors for natural curing to obtain phosphogypsum unfired bricks.
8. The method for preparing phosphogypsum unfired bricks according to claim 7, characterized in that: In step S2, the amount of water added is 8% to 12% of the weight of the dry mix, and the moisture content of the brick is controlled within 15%.
9. The method for preparing phosphogypsum unfired bricks according to claim 7, characterized in that: In step S2, the pressing method is static pressing; the static pressing pressure is 10-30 MPa, and the pressure is maintained for 1-3 min.
10. The method for preparing phosphogypsum unburned bricks according to claim 7, characterized in that: In step S3, the natural curing time is 7 to 14 days.